EFEKTIVITAS SISTEM PRESENSI E-OFFICE OGAN KOMERING ULU CERDAS, INOVATIF DAN EFISIEN (E-OFFICE OKU CINDE) PADA DISIPLIN PEGAWAI NEGERI SIPIL DI SATUAN POLISI PAMONG PRAJA KABUPATEN OGAN KOMERING ULU - Rendi Pahmi Prayuda; Rakhmat Saleh; Yahnu Wiguno Sanyoto (PT. Hasba Edukasi Mandiri, 2026)
E-office OKU CINDE is a website-based application and application used by the Ogan Komering Ulu Regency Government to manage State Civil Apparatus (ASN) starting from attendance, and performance measurement. This application allows the government to act practically because ASN data collection can be done online. In its implementation, there are still misuses such as the use of fake locations, being late, without information and not using faces when filling in attendance. This study uses a descriptive qualitative method with data collection techniques consisting of interviews, documentation and observation. This study was conducted from May 15 - June 20, 2025. The study uses the theory of effectiveness which has indicators of goal achievement, integration and adaptation. The results of this study show that the OKU CINDE e-office has not been effective in the discipline of civil servants of the Ogan Komering Ulu Regency Civil Service Police Unit. There are still employees who are subject to light and moderate disciplinary sanctions in 2024 starting from violations of late attendance, without information, use of fake locations, attendance photos that do not match the face concerned, and violations of other provisions. While in the implementation of the application there are still errors, inadequate servers and quantity of human resources.